2017
DOI: 10.1080/19420862.2017.1402997
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, response and outcome of high-risk neuroblastoma patients treated with long-term infusion of anti-GD2 antibody ch14.18/CHO

Abstract: Immunotherapy with short term infusion (STI) of monoclonal anti-GD2 antibody (mAb) ch14.18 (4 × 25 mg/m2/d; 8–20 h) in combination with cytokines and 13-cis retinoic acid (RA) prolonged survival in high-risk neuroblastoma (NB) patients. Here, we investigated long-term infusion (LTI) of ch14.18 produced in Chinese hamster ovary cells (ch14.18/CHO; 10 × 10 mg/m2; 24 h) in combination with subcutaneous (s.c.) interleukin-2 (IL-2) in a single center program and report clinical response, toxicity and survival. Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(102 citation statements)
references
References 21 publications
6
82
1
13
Order By: Relevance
“…Therefore, the prolongation of the time of Ab infusion was evaluated when five to six cycles of ch14.18/CHO were given at 100 mg/m 2 /cycle as 10‐day continuous long‐term infusion (LTI) in combination with scIL‐2 and oral 13‐cis retinoic acid (RA). Objective clinical response and survival of treated patients showed clinical activity and efficacy in high‐risk NB patients as compared to historical controls . We also observed a lower frequency of neuropathic pain with LTI versus STI (37.7% vs. 51.8%, respectively) and other adverse events of Grade ≥3 were also less frequent in our cohort compared to STI: capillary leak syndrome (13.2% vs. 22.6%), pyrexia (9.4% vs. 38.7%), hypoxia (5.7 vs. 13.1%), diarrhea (3.8 vs. 13.1%), and hypotension (1.9 vs. 17.5%) …”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Therefore, the prolongation of the time of Ab infusion was evaluated when five to six cycles of ch14.18/CHO were given at 100 mg/m 2 /cycle as 10‐day continuous long‐term infusion (LTI) in combination with scIL‐2 and oral 13‐cis retinoic acid (RA). Objective clinical response and survival of treated patients showed clinical activity and efficacy in high‐risk NB patients as compared to historical controls . We also observed a lower frequency of neuropathic pain with LTI versus STI (37.7% vs. 51.8%, respectively) and other adverse events of Grade ≥3 were also less frequent in our cohort compared to STI: capillary leak syndrome (13.2% vs. 22.6%), pyrexia (9.4% vs. 38.7%), hypoxia (5.7 vs. 13.1%), diarrhea (3.8 vs. 13.1%), and hypotension (1.9 vs. 17.5%) …”
Section: Introductionsupporting
confidence: 56%
“…We observed that the frequencies of Treatment Emergent Adverse Events (TEAEs) of Grade ≥3 observed in our cohort were lower compared to STI (4 × 17.5 mg/m 2 , daily 8‐hr infusion on four consecutive days) of ch14.18/SP2/0 (capillary leak syndrome 13.2% vs. 22.6%, pyrexia 9.4% vs. 38.7%, hypoxia 5.7 vs. 13.1%, diarrhea 3.8 vs. 13.1%, hypotension 1.9 vs. 17.5%) . None of the TEAE frequencies of Grade ≥3 reported in the study with STI of ch14.18/SP2/0 2 were lower compared to LTI of ch14.18/CHO . In particular, we observed a lower frequency of neuropathic pain with LTI vs. STI at 37.7% vs. 51.8%, respectively.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Так, использование различных блоков ПХТ 2-й линии, даже в сочетании с ауто-ТГСК не позволяет преодолеть порог ОВ в 15-20 % [11,17,20]. Внедрение гаплоидентичной трансплантации для больных, достигших хорошего ответа на ПХТ, увеличило 2-летнюю выживаемость до 30 % [21]. Благодаря широкому внедрению иммунотерапии (в частности анти GD2-антител) в сочетании с интерлейкином-2 после проведения гаплотрансплантации стало возможным достичь 40 % 5-летней выживаемости в этой группе больных [22].…”
Section: обсуждение основного результата исследованияunclassified